Students’ Direct Strategies in Speaking English of the Third Graders at Vocational High School of Ma’arif V Kebumen - Hastri Firharmawan; Dwi Heriyanto; Eka Nurhidayat; Yayu Sri Rahayu (English Language Education Department, Universitas Majalengka, 2023)
Speaking strategies are important for effective communication. This study investigated the speaking strategies used by students in English class. The researchers used surveys and interviews to collect data from 60 students at the Vocational High School of Ma’arif V Kebumen. It was done from March-April 2023. The study results show that students have used a variety of direct speaking strategies in purpose to improve their speaking skills. The research identified three types of direct strategies to be used: memory, cognition, and compensation. Among those three types of strategies, three learning activities were the most frequently used: placing, role-playing, and mother tongue. The study suggests that a combination of the types of direct strategies can be effective in improving speaking skills. Teachers should consider using various strategies to help their students improve their speaking skills.